Does Music Influence the Multisensory Tasting Experience?. Issue 5 (26th August 2015) - Reinoso Carvalho, Felipe; Van Ee, Raymond; Rychtarikova, Monika; Touhafi, Abdellah; Steenhaut, Kris; Persoone, Dominique; Spence, Charles; Leman, Marc
<x xml:space="preserve">Abstract</x> Abstract All of the senses can potentially contribute to the perception and experience of food and drink. Sensory influences come both from the food or drink itself, and from the environment in which that food or drink is tasted and consumed. In this study, participants initially had to pair each of three soundtracks with one of three chocolates (varying on the bitter‐sweet dimension). In a second part of the study, the impact of the various music samples on these participants' ratings of the taste of various chocolates was assessed. The results demonstrate that what people hear exerts a significant influence over their rating of the taste of the chocolate. Interestingly, when the results were analysed based on the participants' individual music‐chocolate matches (rather than the average response of the whole group), more robust crossmodal effects were revealed. These results therefore provide support for the claim that ambient sound influences taste judgments, and potentially provide useful insights concerning the future design of multisensory tasting experiences. Practical Applications The approach outlined here follows the increasing demand from the field of gastronomy for greater influence over the general multisensory atmosphere surrounding eating/drinking experiences. One of the novel contributions of the present research is to show how, by considering a participant's individual response, further insight for user‐studies in gastrophysics may be provided. Increasing the personalization of such experiments in the years to come may help researchers to design individualized "sonic seasoning" experiences that are even more effective. In the future, then, the approach outlined here may help researchers and experience designers to obtain more profound effects of the auditory or multisensory atmosphere.